2020
DOI: 10.2147/ijn.s270147
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nanomechanics and Histopathology as Diagnostic Tools to Characterize Freshly Removed Human Brain Tumors</p>

Abstract: Background: The tissue-mechanics environment plays a crucial role in human brain physiological development and the pathogenesis of different diseases, especially cancer. Assessment of alterations in brain mechanical properties during cancer progression might provide important information about possible tissue abnormalities with clinical relevance. Methods: With atomic force microscopy (AFM), the stiffness of freshly removed human brain tumor tissue was determined on various regions of the sample and compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…It is necessary to understand all the mechanisms related to the induction and regulation of immune and inflammatory responses to H. pylori [ 2 , 15 , 16 , 17 ]. In recent years, scientific studies have appeared stating that the dysfunction of physiological processes during infection, mostly development of inflammation generates the changes in cells and tissues, which leads to changes in their rheological properties that might lead toward cancer development [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The information on the nanomechanical aspects of the pathological state of H. pylori gastric infection could be of key importance in the development of new bacterial eradication methods, preventive and diagnostic measures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is necessary to understand all the mechanisms related to the induction and regulation of immune and inflammatory responses to H. pylori [ 2 , 15 , 16 , 17 ]. In recent years, scientific studies have appeared stating that the dysfunction of physiological processes during infection, mostly development of inflammation generates the changes in cells and tissues, which leads to changes in their rheological properties that might lead toward cancer development [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The information on the nanomechanical aspects of the pathological state of H. pylori gastric infection could be of key importance in the development of new bacterial eradication methods, preventive and diagnostic measures.…”
Section: Introductionmentioning
confidence: 99%
“…The information on the nanomechanical aspects of the pathological state of H. pylori gastric infection could be of key importance in the development of new bacterial eradication methods, preventive and diagnostic measures. Lately, more attention has been paid to the mechanical testing of tissue samples to understand thoroughly the physiological and pathological processes occurring at the cell and tissue levels [ 20 , 24 , 25 , 26 ]. All physiological processes and their dysfunctions during the development of infection are associated with structural changes that can be described at various structural/organization levels of tissues, cells, and cell organelles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors were first analyzed as a whole, and were in general described as stiffer than the surrounding normal tissue [ 95 , 96 , 97 , 98 , 99 ], due partly to collagen crosslinking in the ECM by malignant and stromal cells [ 100 , 101 ]. The interplay between cellular and ECM stiffness is all the more crucial due to the mechanoreciprocity between the ECM and the expanding tumor within the surrounding normal tissue.…”
Section: Cell-environment Mechanical Interaction In Cancermentioning
confidence: 99%
“…Because stiffness at the cellular level is associated with cell cytoskeletal remodeling, it was previously suggested that mechanical markers such as cell stiffness might be observed (recorded) before histopathological detection [42] . The mechanical properties of single cells and whole tissues change during diseases such as atherosclerosis, diabetes and many kinds of cancer, including bladder, breast and prostate cancers [ 19 , 21 , 33 , 51 ]. The early detection of premalignant conditions and lesions is also very important in the case of oral cancers, where despite significant advances in cancer treatment, the overall 5-year survival rate has not significantly increased over the past decades [ 4 , 11 ].…”
Section: Introductionmentioning
confidence: 99%